Dicalcium phosphate and Vitamin A for calves on winter bluestem pasture - Smith, E.F.; Richardson, D.; DeGeer, C.V.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The 42 heifer calves, 10 or 11 per treatment, used in this experiment were good to choice Herefords from near Fort Davis, Texas, assigned on a random-weight basis to treatments. They were pastured together in a 150-acre bluestem pasture. During winter, so the three groups could get their experimental rations (Table 19), they were penned and fed three times weekly. Dicalcium phosphate (0.1 pound per heifer daily) and Vitamin A (10,000 I.U. daily)m when fed, were mixed with soybean meal. The experimental rations were discontinued April 3 and only salt was supplied during summer grazing.
Keywords: Beef; Bluestem pasture; Dicalcium phospate; Vitamin A